1999
DOI: 10.1029/1999gl010894
|View full text |Cite
|
Sign up to set email alerts
|

Does molecular HNO3 adsorb onto sulfuric acid droplet surfaces?

Abstract: Abstract. Room temperature surface tension measurements on the ternary system: nitric acid -sulfufic acid -water are reported. There is a dramatic decrease in the surface tension of sulfuric acid -water solutions as nitric acid is added. This decrease is most pronounced in the stratospherically-relevant range of sulfuric acid concentrations, between 50 and 75 wt% sulfuric acid. The surface tension decrease indicates a change in surface energy and surface composition and / or structure associated with partition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 23 publications
5
32
0
Order By: Relevance
“…Recent studies indicate that the surface of an aqueous particle is often enriched in low surface tension components such as molecular nitric acid (38,39) and organic materials (40)(41)(42). This surface adsorption effect in complex particle systems, which exist in the atmosphere, can have a 2-fold effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies indicate that the surface of an aqueous particle is often enriched in low surface tension components such as molecular nitric acid (38,39) and organic materials (40)(41)(42). This surface adsorption effect in complex particle systems, which exist in the atmosphere, can have a 2-fold effect.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is clear from Eqs. 2 and 3 that such surface enrichments (38)(39)(40)(41)(42) will make it more difficult for an ice nucleus to form at the surface layer of an aqueous droplet as compared with that of a pure water droplet. Second, the same surface adsorption effect can enrich the composition of the surface layer to a level where multicomponent solid phases can nucleate and grow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering liquid particle microphysics, we need to take into account the surface enrichment of HNO 3 in both binary HNO 3 =H 2 O and ternary HNO 3 /H 2 SO 4 /H 2 O solutions (Yang and FinlaysonPitts, 2001;Donaldson and Anderson, 1999), which could influence surface-based nucleation rates. In addition, the presence of H 2 SO 4 in STS droplets can strongly inhibit the nucleation of HNO 3 hydrates (Koop et al, 1997b).…”
Section: Article In Pressmentioning
confidence: 99%
“…Specifically, it has been shown that molecular nitric acid is enriched at the surface layer of aqueous solutions (Donaldson and Anderson, 1999;Yang and Finlayson-Pitts, 2001). Furthermore, our recent study (Djikaev et al, 2003) also shows that the level of surface enrichment of a given species in a multicomponent solution is a function of particle size.…”
mentioning
confidence: 99%